Recent Trends on Biosurfactants With Antimicrobial Activity Produced by Bacteria Associated With Human Health: Different Perspectives on Their Properties, Challenges, and Potential Applications - De Giani, Alessandra; Zampolli, Jessica; Di Gennaro, Patrizia (Frontiers in Microbiology, 2021)
The attention towards the bacteria associated with human health is growing more and more, above all regarding the bacteria that inhabit the niches offered by the human body, i.e., gastrointestinal tract, skin, vaginal environment, and lungs. Among the secondary metabolites released by microorganisms associated with human health, little consideration is given to the biosurfactants, molecules with both hydrophobic and hydrophilic nature. Their role in the complex human environment is not only the mere biosurfactant function, but they could also control the microbiota through the quorum sensing system and the antimicrobial activity. These functions protect them and, accordingly, the human body principally from microbial and fungal pathogens. Consequently, nowadays, biosurfactants are emerging as promising bioactive molecules due to their very different structures, biological functions, low toxicity, higher biodegradability, and versatility. Therefore, this review provides a comprehensive perspective of biosurfactants with antimicrobial activity produced by bacteria associated with the human body and related to everything human beings are in contact with, e.g., food, beverages, and food-waste dumping sites. For the first time, it is highlighted the role of an “-omic” approach to predict gene products for biosurfactant production, and an overview of the available gene sequences is reported. Besides, antimicrobial biosurfactants’ features, challenges, and potential applications in the biomedical, food, and nutraceutical industries are discussed.